(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the periodontal condition of patients treated at the Dental School Clinic of the State University of Paraíba – UEPB (as per its Portuguese acronym), campus I, Campina Grande, Paraíba, investigating its association with the social and systemic characteristics of the studied population and identifying the service profile. It is a study cross-sectional quantitative and analytical, which involved collecting data from medical records, using as exclusion criteria the incompleteness of data or the absence of signature of the written informed consent form by the patient. The analyzes were performed by SPSS 20.0. To characterize the population, the data frequencies were distributed. To associate the periodontal condition (gingivitis/periodontitis) and the other variables, the Pearson’s chi-square test (or Fisher’s exact test when appropriate) was used, with p < 0.05. Of the total 426 medical records, 42,5% were excluded, remaining 245 medical records. Of the 245 forms included in the study, 147 (60,0%) patients had some reported systemic disease and 96 (39,2%) had used some type of medication. The association between periodontal condition and other variables was statistically significant between periodontitis and age group from 51 to 64 years old (p < 0.001) and widowed marital status (p < 0.001). During the analysis, there was a record of medication use without a record of the systemic condition and vice versa. A need to improve the filling of dental records is suggested. Furthermore, the determination of periodontal condition, socio-economic-demographic and systemic characteristics demonstrates the importance of strategies to ensure adequate diagnosis, treatment plan and appropriate monitoring.